Potential sources of Triatoma infestans reinfesting peridomiciles identified by morphological characterization in Los Llanos, La Rioja, Argentina - Hernández, María Laura (2013)
The presence of Triatoma infestans in habitats treated with insecticides constitutes a frequent problem in endemic areas. Basing our study on the hypothesis that descendants of a residual population should be more similar to the pre-treatment population than to any other, we compared the indications of two quantitative morphological approaches. This study seeks to find the origin of 247 T. infestans from three populations found in two chicken coops and a goat corral after treatment with insecticides. The results obtained by quantitative morphology suggest that the T. infestans found between three-34 months after the application of insecticides formed mixed populations with insects derived from residual foci and neighbouring habitats. Our analyses also showed the presence of a phenotype which does not resemble neither the pre-treatment phenotype nor the one from neighbouring populations, suggesting the presence of a particular post-treatment phenotype. The heads size showed some variations in males from different populations and remained unchanged in females, which reinforces the hypothesis of an intraspecific competition for food with priority for females. This article presents, for the first time, the combined analysis of geometric morphometry of heads and antennal phenotypes to identify the composition of reinfesting populations.